Biogas production from co-digestion of organic fraction of municipal solid waste and fruit and vegetable waste. (March 2017) - Pavi, Suelen; Kramer, Luis Eduardo; Gomes, Luciana Paulo; Miranda, Luis Alcides Schiavo
Highlights: The organic fraction of municipal solid waste (OFMSW) was co-digested with fruit and vegetable waste (FVW). The highest cumulative biogas and methane yields were obtained with a 1/3 ratio of OFMSW to FVW. The digestion occurred in a stable manner for all OFMSW/FVW ratios tested. Abstract: The anaerobic co-digestion of organic fraction of municipal solid waste (OFMSW) and fruit and vegetable waste (FVW) was evaluated in terms of biogas and methane yield, volatile solids (VS) removal rate and stability of the process. The batch experiment was conducted in mesophilic conditions (35 °C), with four different OFMSW/FVW ratios (VS basis) of 1/0, 1/1, 1/3, and 0/1. The methane yield from the co-digestion was higher than the mono-digestion for OFMSW and FVW. The optimal mixing ratio of OFMSW/FVW was found to be 1/3. The average cumulative biogas and methane yield in this condition was 493.8 N mL/g VS and 396.6 N mL/g VS, respectively, and the VS removal rate was 54.6%. Compared with the mono-digestion of OFMSW and FVW, the average increase in methane yield was 141% and 43.8%, respectively.